Characterization of the parietal intestinal microbiota in colon cancer - S. V. Volkov; S. L. Lobanov (Сибирский научный медицинский журнал, 2021)
Introduction. Colon cancer (RCC) clinically manifests itself in the late stages, therefore, early diagnosis presents significant difficulties. There are many types of microorganisms in the human colon that form symbiosis with intestinal cells to maintain normal function. Аim of the study was to determine the composition of the parietal microflora of the colon under conditions of a tumor process and to assess the possibility of using these data in the diagnosis of colon cancer. Material and methods. The main group included 63 patients operated on for cancer (adenocarcinoma) of the left half of the colon (descending, sigmoid, rectosigmoid regions) with I T1-2N0M0, II T3-4aN0M0, III T1-2N1M0 stages of the tumor process. Among them are 32 men and 31 women aged 20 to 75 years (57.7 ± 3.8 years). In all patients, before hospitalization, the tumor was confirmed by colonoscopy followed by histological examination. The group of clinical comparison in the amount of 25 people consisted of patients with chronic hemorrhoids without exacerbation, who underwent colonoscopy. Material from the main group, biopsies of tumor tissue and visually unchanged colon mucosa, were taken intraoperatively during tumor removal. In patients of the clinical comparison group, the material was taken during the colonoscopy process. The composition of the intestinal microbiota was determined by a bacteriological method. Results and discussion. As a result of comparing the colon microbiota of cancer patients and the clinical comparison group, statistically significant differences in the quantitative composition of Lactobacillus spp., Bifidobacterium spp., Bacteroides spp., Clostridium spp., Enterococcus spp., Escherichia coli (typical), Escherichia coli (lactose-negative), Enterobacteriaceae, Staphylococcus spp. (CNS), Candida spp. It was established for the first time that Bifidobacterium spp., Enterococcus spp. and the age of the patient can be further used in the diagnosis of a malignant process. Conclusion. The created additive model can be used as an additional screening criterion in the early diagnosis of colon cancer.